The Concept of Wahdaniyah Allah Perspective of Muhammad Nafis in the Book of Ad-Durrun Nafis as an Effort to Instill Aqidah in Early Childhood Generation Alfa - Abd Rahman; Ira Suryani; Nelly Rahmia; Khofifah Indar Rahman; Didi Maslan (Universitas Muhammadiyah Enrekang, 2022)
Wahdaniyah means the oneness of the substance of Allah SWT, singular and not numbered. Every Muslim needs to understand and believe in it, especially the alpha generation, the generation born in the midst of sophisticated technological advances. Parents need to make special efforts so that the alpha generation can be instilled with God's divine qualities. This study uses the library research method with the results of the research that in the book Addurrun Nafis wahdaniyah is the Oneness of Allah SWT which is divided into 4 parts which have the same meaning as the word One for Allah, namely: Oneness of Deeds (Tauhidul Af'al) , Oneness of Names (Tauhidul Asma'), Oneness of Nature (Tauhidush Shifat), Oneness of Essence (Tauhidudz Dzat. Efforts to instill faith in early childhood alpha generation are by the method of praying, advising, teaching, tell stories, and singing